ESR/ERS white paper on lung cancer screening - Kauczor, Hans-Ulrich (Eur Radiol, 2015)
ABSTRACT: Lung cancer is the most frequently fatal cancer, with poor survival once the disease is advanced. Annual low-dose computed tomography has shown a survival benefit in screening individuals at high risk for lung cancer. Based on the available evidence, the European Society of Radiology and the European Respiratory Society recommend lung cancer screening in comprehensive, quality-assured, longitudinal programmes within a clinical trial or in routine clinical practice at certified multidisciplinary medical centres. Minimum requirements include: standardised operating procedures for low-dose image acquisition, computer-assisted nodule evaluation, and positive screening results and their management; inclusion/exclusion criteria; expectation management; and smoking cessation programmes. Further refinements are recommended to increase quality, outcome and cost-effectiveness of lung cancer screening: inclusion of risk models, reduction of effective radiation dose, computer-assisted volumetric measurements and assessment of comorbidities (chronic obstructive pulmonary disease and vascular calcification). All these requirements should be adjusted to the regional infrastructure and healthcare system, in order to exactly define eligibility using a risk model, nodule management and a quality assurance plan. The establishment of a central registry, including a biobank and an image bank, and preferably on a European level, is strongly encouraged. KEY POINTS: • Lung cancer screening using low dose computed tomography reduces mortality. • Leading US medical societies recommend large scale screening for high-risk individuals. • There are no lung cancer screening recommendations or reimbursed screening programmes in Europe as of yet. • The European Society of Radiology and the European Respiratory Society recommend lung cancer screening within a clinical trial or in routine clinical practice at certified multidisciplinary medical centres. • High risk, eligible individuals should be enrolled in comprehensive, quality-controlled longitudinal programmes.